The Portrait of Kuta village Community Economic Activities and Its Application as Economic Learning Source Based on Cultural Values (Dinamika Pendidikan, 2016)
This research aims to improve students’ knowledge and understanding on pattern development of economic activity on community that retain its local wisdom. Kuta village is located at Karangpaningal Village, Tambaksari District, Ciamis Regency. It is one of traditional villages which still maintains its traditions in harmony with nature. The research was a qualitative study and data were collected by using interviews, observation, and literature study. Findings show that there is a development of the community’s livelihood at Kuta Village. The scope of economic activity is still in micro scale. Then, there is a technological transformation in natural resource management. Therefore, it is very clear that local wisdom is very suitable for subject materials in the form of narratives, stories, posters, or comics.